Production of multifunctional lipases by Penicillium verrucosum and Penicillium brevicompactum under solid state fermentation of babassu cake and castor meal - Silva, Marceli Fernandes; Freire, Denise M. G; de Castro, Aline Machado; Di Luccio, Marco; Mazutti, Marcio A; Oliveira, J. Vladimir; Treichel, Helen; Oliveira, Débora (Bioprocess and biosystems engineering, 2011)
The main objective of this work was to optimize lipase production, in terms of hydrolytic and esterification activities, by Penicillium brevicompactum and Penicillium verrucosum in solid state fermentation using agroindustrial residues as raw material. Maxima hydrolytic activities of 48.6 and 87.7 U/g were achieved when P. brevicompactum was cultured in babassu cake and castor meal, respectively. Higher esterification activities (around 244 U/g) were achieved when P. brevicompactum was used as microorganism and babassu cake as raw material. Different experimental conditions led to these promising values, clearly showing that no correlation can be attributed between hydrolytic and esterification activities. In spite of the several applications of lipases which are capable of catalyze synthesis reactions, only few works in this subject are presented in the literature, especially when low cost raw materials are used.